PENGARUH KARAKTERISTIK PEKERJAAN, BUDAYA ORGANISASI DAN KUALITAS INTERAKSI ATASAN DAN BAWAHAN TERHADAP KINERJA MELALUI PERILAKU BEKERJA KARYAWAN DI PTPN XII SURABAYA - Sitio, Alexander; Titisari, Purnami; Tobing, Diana Sulianti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract: The purpose of this study was to analyze the effect of job characteristics, organizational culture, and interaction between superiors and subordinates on employees performance and behavior at PT Perkebunan Nusantara (PTPN) XII Surabaya. The population in this research was all 300 employees at PTPN XII Surabaya with the sample consisted of 90 respondents. Results showed that job characteristics, organizational culture, and interaction between superiors and subordinates had significant effect on employees performance and behavior. Keywords: Job Characteristics, Organizational Culture, Interaction Superiors and Subordinates, Work Behavior, and Performance of Employees.